If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3(6 + 2x) = 0 6 + (6 * -3 + 2x * -3) = 0 6 + (-18 + -6x) = 0 Combine like terms: 6 + -18 = -12 -12 + -6x = 0 Solving -12 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -6x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -6x = 0 + 12 -6x = 0 + 12 Combine like terms: 0 + 12 = 12 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| 0=-16t^2+245 | | 7(y-8)=9y-56 | | 10+5(2-2x)=0 | | h=245+16x^2 | | 245=-16t^2+h | | y=(2y)+15 | | 7x+21x-8=7(4x+9) | | (y^2+4y+4)(y+2)= | | 2x^3=129 | | 8m-7=5m+11 | | z(t)=120(1/2)^t/32760 | | -16t^2-h+245=0 | | 6=1-3z | | 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 | | 5x-40=8x+11 | | 28-4x=13-9x | | -161+8x=2x+99 | | 12x+15=5x+7 | | (x-1)+(x-1)=g |